Clothing biosensory engineering - Li, Yi; Wong, A. S. W. (Anthony S. W.) (Woodhead publishing in textiles., 2006)
Human sensory perception of clothing involves a series of complex interactive processes, including physical responses to external stimuli, neurophysiological processes for decoding stimuli through the biosensory and nervous systems inside the body, neural responses to psychological sensations, and psychological processes for formulating preferences and making adaptive feedback reactions. Clothing biosensory engineering is a systematic and integrative way of translating consumers' biological and sensory responses, and psychological feelings and preferences about clothing, into the perceptual elements of design. It is a link between scientific experimentation and commercial application to develop economic solutions to practical technical problems. Clothing biosensory engineering quantifies the decision-making processes through which physics, mathematics, neurophysiological and engineering techniques are applied to optimally convert resources to meet various sensory requirements - visual/thermal/mechanical. It includes theoretical and experimental observations, computer simulations, test methods, illustrations and examples of actual product development. Describes the process of Clothing biosensory engineering in detailQuantifies the decision making processes applied to optimally convert resources to meet various sensory requirementsIncludes theoretical and experimental observations and examples of actual product development.